Integration of Transcriptome, Gross Morphology and Histopathology in the Gill of Sea Farmed Atlantic Salmon (Salmo salar): Lessons From Multi-Site Sampling - Król, Elżbieta; Noguera, Patricia; Shaw, Sophie; Costelloe, Eoin; Gajardo, Karina; Valdenegro, Victoria; Bickerdike, Ralph; Douglas, Alex; Martin, Samuel A. M. (Frontiers in Genetics, 2020)
The gill of teleost fish is a multifunctional organ involved in many physiological processes such as gas exchange, osmotic and ionic regulation, acid-base balance and excretion of nitrogenous waste. Due to its extensive interface with the environment, the gill plays a key role as a primary mucosal defence tissue against pathogens, as manifested by the presence of the gill-associated lymphoid tissue (GIALT). In recent years, the prevalence of multifactorial gill pathologies has increased significantly, causing substantial losses in Atlantic salmon aquaculture. The transition from healthy to unhealthy gill phenotypes and the progression of multifactorial gill pathologies, such as proliferative gill disease (PGD), proliferative gill inflammation (PGI) and complex gill disorder (CGD), are commonly characterised by epithelial hyperplasia, lamellar fusion and inflammation. Routine monitoring for PGD relies on visual inspection and non-invasive scoring of the gill tissue (gross morphology), coupled with histopathological examination of gill sections. To explore the underlying molecular events that are associated with the progression of PGD, we sampled Atlantic salmon from three different marine production sites in Scotland and examined the gill tissue at three different levels of organisation: gross morphology with the use of PGD scores (macroscopic examination), whole transcriptome (gene expression by RNA-seq) and histopathology (microscopic examination). Our results strongly suggested that the changes in PGD scores of the gill tissue were not associated with the changes in gene expression or histopathology. In contrast, integration of the gill RNA-seq data with the gill histopathology enabled us to identify common gene expression patterns associated with multifactorial gill disease, independently from the origin of samples. We demonstrated that the gene expression patterns associated with multifactorial gill disease were dominated by two processes: a range of immune responses driven by pro-inflammatory cytokines and the events associated with tissue damage and repair, driven by caspases and angiogenin.